Performance assessment of plant extracts as green demulsifiers - Yaakob, A.B. (Japan Petroleum Institute, 2017)
Crude oil dehydration is an important requirement in oil and gas processing. Most of the conventional chemical demulsifiers are effective in resolving water-in-oil (W/O) emulsions but their application is restricted due to environmental concerns. The chemical demulsifiers are toxic and may cause serious environmental degradation during water disposal. In this study, we have investigated extracts of green tea and some vegetable oils such as the olive and coconut oils as potential environment-friendly W/O demulsifiers. The plant extract was obtained by Soxhlet extraction method while the vegetable oil triglycerides was obtained from 100 coconut oil. The purity and compositions of the extracts and the vegetable oils were obtained with high temperature gas chromatography (HTGC) while the toxicity tests were also carried out to ascertain the eco-friendliness of the tested potential demulsifiers. The melting point of the water-insoluble and unreactive coconut oil was 76 °F while its specific gravity was 0.9. Subsequently, bottle tests were conducted under static and dynamic conditions to select the best demulsifier among the extract and the vegetable oils. Results showed that the coconut oil gave a higher volume of separated water than the green tea extract and olive oil for all W/O emulsion samples. © 2017, Japan Petroleum Institute. All rights reserved.